Root Morphologycal Responses of Oil Palm (Elaeis guineensis Jacq.) Hybrids to Copper Toxicity - Dwi Nur Shinta Febriani; Eka Tarwaca Susila Putra; Tohari Tohari (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2017)
The experiment aimed to identify the root response of eight oil palm hybrids to copper toxicity. The factorial treatments were arranged in Randomized Completely Block Design with three blocks as replication. The first factor was the copper toxicity, while eight oil palm hybrids (DxP) consisted of Yangabi (P1), Avros (P2), Langkat (P3), PPKS 239 (P4), Simalungun (P5), PPKS 718 (P6), PPKS 540 (P7), and Dumpy (P8) as second factor. Root growth variables were observed, including total root length, total root area, root volume and diameter, copper content on root, fractal dimension, relative root water content, fresh root weight, and root dry weight. Data were analysed using analysis of variance (ANOVA) and continued with Duncan’s Multiple Range Test at α=5%. There was a declinning in total root length, volume and diameter, fresh and dry weight as the copper content rose on the root tissue, but no significant different was found in total root area.